Management Control Systems in SMEs: A Case Study Using Otley’s Performance Management Framework - Daryl Quinco (Research Synergy Foundation, 2026)
This study explores the management control systems (MCS) within a small family-owned furniture retail business using Otley’s (1999) performance management framework. Limited research on SMEs examines how informal and relationship-based controls interact with formal performance management mechanisms in family-owned enterprises. The case study adopts a qualitative, exploratory approach to examine how the business aligns its objectives, strategies, target setting, reward systems, and feedback loops to optimize its operations and achieve long-term sustainability. Data collection involved semi-structured interviews with the owner and 3 personnel, along with on-site observations, yielding rich insights into the informal and formal controls at play. The findings reveal that while the business emphasizes family-oriented objectives and informal decision-making, there are significant opportunities to improve financial planning, performance monitoring, and strategic alignment. The lack of formalized systems leads to inconsistencies in budgeting, performance tracking, and employee motivation. However, the case also highlights the strengths of flexible, relationship-based controls, which foster unity and adaptability in a family business context. The study suggests that SMEs can benefit from integrating formal MCS with their existing informal practices to strike a balance between efficiency and cultural alignment. The findings contribute to the understanding of MCS design in SMEs by illustrating how Otley’s framework operates in a single-case SME and highlighting the hybrid nature of formal and informal control mechanisms. The study, therefore, provides practical SME insights for improving performance management practices in family-owned enterprises operating under similar organizational conditions.